Premature ovarian failure - Tkaczuk-Włach, Joanna; Sobstyl, Małgorzata; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2011)
Premature ovarian failure (POF) is a syndrome characterized by amenorrhoea, high levels of gonadotropins (FSH and LH) and hypoestrogenism before the age of 40. It is a disorder affecting approximately 1% of women. The known causes include: genetic – X chromosome abnormalities and autosomal genetic conditions, autoimmune conditions, and iatrogenic and environmental factors. Management involves hormone replacement therapy and infertility treatment.